Blood Pressure Changes in Relation to Arsenic Exposure in a U.S. Pregnancy Cohort - Farzan, Shohreh F. (Environ Health Perspect, 2015)
BACKGROUND: Inorganic arsenic exposure has been related to the risk of increased blood pressure based largely on cross-sectional studies conducted in highly exposed populations. Pregnancy is a period of particular vulnerability to environmental insults. However, little is known about the cardiovascular impacts of arsenic exposure during pregnancy. OBJECTIVES: We evaluated the association between prenatal arsenic exposure and maternal blood pressure over the course of pregnancy in a U.S. population. METHODS: The New Hampshire Birth Cohort Study is an ongoing prospective cohort study in which > 10% of participant household wells exceed the arsenic maximum contaminant level of 10 μg/L established by the U.S. EPA. Total urinary arsenic measured at 24–28 weeks gestation was measured and used as a biomarker of exposure during pregnancy in 514 pregnant women, 18–45 years of age, who used a private well in their household. Outcomes were repeated blood pressure measurements (systolic, diastolic, and pulse pressure) recorded during pregnancy. RESULTS: Using linear mixed effects models, we estimated that, on average, each 5-μg/L increase in urinary arsenic was associated with a 0.15-mmHg (95% CI: 0.02, 0.29; p = 0.022) increase in systolic blood pressure per month and a 0.14-mmHg (95% CI: 0.02, 0.25; p = 0.021) increase in pulse pressure per month over the course of pregnancy. CONCLUSIONS: In our U.S. cohort of pregnant women, arsenic exposure was associated with greater increases in blood pressure over the course of pregnancy. These findings may have important implications because even modest increases in blood pressure impact cardiovascular disease risk. CITATION: Farzan SF, Chen Y, Wu F, Jiang J, Liu M, Baker E, Korrick SA, Karagas MR. 2015. Blood pressure changes in relation to arsenic exposure in a U.S. pregnancy cohort. Environ Health Perspect 123:999–1006; http://dx.doi.org/10.1289/ehp.1408472